A Review In Improving Quality In Healthcare: To Makes A Satisfied Patient - Abdullah Eid Nafe Alrashidi , Alia Salama Mohsen Al-Huwaiti , Rasmyah Rashid Albalawi , Abdullah Banyan Shabib Al-Dosari , Ajaieb Aday Aldhafiri; Gehan Salamah Al Hawiti , Ali Faraj Ali Alyami , Ruqayyah Hussain Hussain , Khaled Abdul Rahman Khaled Al-Ruwais (Migration Letters, 2022)
Background Efforts to improve the quality, safety, and efficiency of health care provision have often focused on changing approaches to the way services are organized and delivered. Continuous quality improvement (CQI), an approach used extensively in industrial and manufacturing sectors, has been used in the health sector. Despite the attention given to CQI, uncertainties remain as to its effectiveness given the complex and diverse nature of health systems. This review assesses the effectiveness of CQI across different health care settings, investigating the importance of different components of the approach. Methods We searched 11 electronic databases: MEDLINE, CINAHL, EMBASE, AMED, Academic Search Complete, HMIC, Web of Science, PsycINFO, Cochrane Central Register of Controlled Trials, LISTA, and NHS EED to February 2019. Also, we searched reference lists of included studies and systematic reviews, as well as checking published protocols for linked papers. We selected randomized controlled trials (RCTs) within health care settings involving teams of health pr[1]ofessionals, evaluating the effectiveness of CQI. Comparators included current usual practice or different strategies to manage organizational change. Outcomes were health care professional performance or patient outcomes. Studies were published in English. Results Twenty-eight RCTs assessed the effectiveness of different approaches to CQI with a non-CQI comparator in various settings, with interventions differing in terms of the approaches used, their duration, meetings held, people involved, and training provided. All RCTs were considered at risk of bias, undermining their results. Findings suggested that the benefits of CQI compared to a non-CQI comparator on clinical process, patient, and other outcomes were limited, with less than half of RCTs showing any effect. Where benefits were evident, it was usually on clinical process measures, with the model used (i.e., Plan-Do-Study-Act, Model of Improvement), the meeting type (i.e., involving leaders discussing implementation) and their frequency (i.e., weekly) having an effect. None considered socio-economic health inequalities. Conclusions Current evidence suggests the benefits of CQI in improving health care are uncertain, reflecting both the poor quality of evaluations and the complexities of health services themselves. Further mixed-methods evaluations are needed to understand how the health service can use this proven approach.